(untitled) (ModaPalavra e-periódico, 2013)
In the purpose of understanding how the relationship between classical ballet and fashion stands, this article makes use of the bibliographic research methodology, drawing an outlook above classical ballet aesthetic and traditional costumes. Its theoretical background is composed of renowned authors from dance and artistic productions scene, in which is centered the development of this study. The research intends to expose the links between ballet and fashion, explaining how these elements and their properties interact with the human figure in a dance act, and evidencing the relevant aspects on proceedings of costume creation.